Superconductor terahertz metamaterials - Srivastava, Yogesh Kumar (2019)
Terahertz metamaterials showcase tremendous potential for plethora of applications ranging from biochemical sensing, high-speed wireless communication, and efficient modulators. Conventional terahertz metamaterials are made of noble metals. Incorporating superconductors in terahertz metamaterials potentially provide unprecedented opportunities to control resonance features which has huge implications in the real-world technologies. This thesis reports on new applications of superconducting terahertz metamaterials for ultra-low loss operation, ultrafast manipulation of electromagnetic radiation and novel quantum effects. This work experimentally and numerically demonstrates that the quality factor of a low asymmetry Fano resonant asymmetric split ring metamaterial is extremely sensitive to the conductivity of the constituent materials. At low asymmetry regime even high conductivity noble metals fail to support Fano resonance excitation. The metamaterials designed using high-Tc superconductors provide access to the extremely low asymmetry regime and excites extremely sharp Fano resonances. Highest Q factor achieved with superconducting resonator (167) found to be two-fold in comparison to metallic resonators (84). There is a clear advantage of superconducting resonators sustaining high Q Fano resonances compared to conventional metals in designing low loss metamaterials at terahertz frequencies.